Genetic and evolutionary computing : proceedings of the tenth International Conference on Genetic and Evolutionary Computing, November 7-9, 2016 Fuzhou City, Fujian Province, China - Pan, Jeng-Shyang; Lin, Jerry Chun-Wei; Wang, Chia-Hung; Jiang, Xin Hua (Springer, 2017)
This book gathers papers presented at the 10th International Conference on Genetic and Evolutionary Computing (ICGEC 2016). The conference was co-sponsored by Springer, Fujian University of Technology in China, the University of Computer Studies in Yangon, University of Miyazaki in Japan, National Kaohsiung University of Applied Sciences in Taiwan, Taiwan Association for Web Intelligence Consortium, and VSB-Technical University of Ostrava, Czech Republic. The ICGEC 2016, which was held from November 7 to 9, 2016 in Fuzhou City, China, was intended as an international forum for researchers and professionals in all areas of genetic and evolutionary computing.
Keywords: Genetic programming (Computer science) -- Congresses.; Genetic algorithms -- Congresses.; Evolutionary computation -- Congresses.; elektronické knihy; electronic books